(untitled) (Bangladesh Journal of Pharmacology, 2015)
In the present study, the effect of ursolic acid benzaldehyde chalcone (UABC) on ovarian carcinoma cells was studied. The results revealed that ovarian carcinoma cells on UABC treatment increased Sub-G1 cell population, increased rate of cell apoptosis and morphological changes in mitochondrial membrane. In OVCAR 432 cells treatment with UABC increased the Sub-G1 cell population to 72.3% and growth inhibition rate of >72%. Treatment with 20 µM of UABC for 48 hours, led to an induction of apoptosis in 67.2% and induced morphological changes in OVCAR 432 cells. The Western blot results showed high concentration of cytochrome c in the cell cytosol after 48 hours of UABC treatment. Treatment of RMS-13 cells with UABC resulted in inhibition of GLI1, GLI2, PTCH1, and IGF2 genes. In addition, we found a significant reduction in hedgehog activity of RMS-13 cells after UABC treatment by means of a hedgehog-responsive reporter assay. Therefore, UABC can be a promising agent for the treatment of ovarian carcinoma.